The future of the dollar - Helleiner, Eric, 1963-; Kirshner, Jonathan (Cornell studies in money., 2009)
Explores possible futures of the dollar as an international currency as the dollar becomes more volatile than ever against foreign currencies, and China and the Arab Gulf states hold more United States government obligations.